How Do CD4+ T Cells Detect and Eliminate Tumor Cells That Either Lack or Express MHC Class II Molecules? - Haabeth, Ole Audun Werner; Tveita, Anders Aune; Fauskanger, Marte; Schjesvold, Fredrik; Lorvik, Kristina Berg; Hofgaard, Peter O.; Omholt, Hilde; Munthe, Ludvig A.; Dembic, Zlatko; Corthay, Alexandre; Bogen, Bjarne (Frontiers in Immunology, 2014)
CD4+ T cells contribute to tumor eradication, even in the absence of CD8+ T cells. Cytotoxic CD4+ T cells can directly kill MHC class II positive tumor cells. More surprisingly, CD4+ T cells can indirectly eliminate tumor cells that lack MHC class II expression. Here, we review the mechanisms of direct and indirect CD4+ T cell-mediated elimination of tumor cells. An emphasis is put on T cell receptor (TCR) transgenic models, where anti-tumor responses of naïve CD4+ T cells of defined specificity can be tracked. Some generalizations can tentatively be made. For both MHCIIPOS and MHCIINEG tumors, presentation of tumor-specific antigen by host antigen-presenting cells (APCs) appears to be required for CD4+ T cell priming. This has been extensively studied in a myeloma model (MOPC315), where host APCs in tumor-draining lymph nodes are primed with secreted tumor antigen. Upon antigen recognition, naïve CD4+ T cells differentiate into Th1 cells and migrate to the tumor. At the tumor site, the mechanisms for elimination of MHCIIPOS and MHCIINEG tumor cells differ. In a TCR-transgenic B16 melanoma model, MHCIIPOS melanoma cells are directly killed by cytotoxic CD4+ T cells in a perforin/granzyme B-dependent manner. By contrast, MHCIINEG myeloma cells are killed by IFN-γ stimulated M1-like macrophages. In summary, while the priming phase of CD4+ T cells appears similar for MHCIIPOS and MHCIINEG tumors, the killing mechanisms are different. Unresolved issues and directions for future research are addressed.